A Preliminary User Interface for Software Vendor Analysis and Selection Tool - Müller, Tormod, Mork; Rani, Anshul; Mishra, Deepti (CCSD, 2024)
Part 5: Demos International audience In software ecosystems, the decision-making process for vendor selection remains a significant challenge, often worsened by the lack of effective tools that leverage visualization to aid in these decisions. This study aims to bridge this gap by prototyping a tool and hence proposing a user interface for the same, based on a software vendor selection framework, enhancing decision-making through intuitive visualizations and a user-friendly interface. Our research methodology combined a semi-structured literature review, preliminary user interface development, and expert feedback to ensure the tool’s practicality and effectiveness. The prototype testing of the user interface design, informed by expert feedback, indicates a positive impact on decision-making processes, demonstrating the prototype’s ability to streamline vendor analysis and selection. The proposed tool significantly contributes to reducing the complexity and subjectivity of vendor selection, offering a more structured and data-driven approach.